Knowledge, Beliefs, and Practices Related to Menstruation Among Female Students in Afghanistan - Sakhi R; Jalalzai S; Ahmadi Z; Almaszada R; Zarghoon FN; Mohammadi R; Ahmad H; Mazhar S; Faqirzada M; Hamidi M (Dove Medical Press, 2023)
Rohullah Sakhi, Shakila Jalalzai, Zainab Ahmadi, Rowaida Almaszada, Froogh Nazanin Zarghoon, Raihana Mohammadi, Habiba Ahmad, Shakila Mazhar, Maryam Faqirzada, Mozhda Hamidi Public Health Faculty, Kabul University of Medical Sciences, Kabul, AfghanistanCorrespondence: Habiba Ahmad, Public Health Faculty, Kabul University of Medical Sciences, Ata Turk Avenue, 3rd District, Kabul, Afghanistan, Email habibaahmad241@gmail.comBackground: Menstruation is a universal, natural, unique, and physiological phenomenon. Despite the fact that menstruation is a natural fact of life, it is still considered taboo in Afghanistan and other developing countries.Objective: To assess knowledge, beliefs, and practices related to menstruation among female students of Kabul University of Medical Sciences (KUMS).Methods: A cross-sectional descriptive study design was conducted at KUMS in 2022, and a quota sampling technique was used.Results: In this study, 339 students participated out of the 346-sample size. The majority of participants (70.02%), were over 20 years of age. About (59.60%) of participants were aware of menstruation before menarche. The main source of their information was their mothers (37.50%). The average age of menarche was 13.5 years old. Above 70% of respondents had normal patterns of menstruation. More than half of them (51.90%) had dysmenorrhea. Frequent menstrual disorders were abdominal pain (58.1%), and backache (56.1%). The majority of respondents had good and acceptable knowledge of menstruation (33.6%), and (63.1%) respectively. A statistically significant relationship between knowledge and academic year was observed (P value = 0.005). The majority of respondents (92.6%) had poor menstrual beliefs. A statistically significant relationship between respondents' age and beliefs was observed (P value = 0.004). Mother education did not affect respondents' level of beliefs (P value = 0.4). In addition, respondents had good practice of menstruation (75%).Conclusion: In general participants had a good and acceptable level of knowledge with good practice related to menstruation. Despite the good knowledge and practice, the respondents' beliefs related to menstruation were poorer than what was expected from medical disciplines students. Their frequent source of information was their mothers, which highlights the provision of information and education for mothers and all females.Keywords: menstruation, knowledge, beliefs, practice, female students, Kabul University of Medical Sciences